Pengaruh Paparan Asap Rokok terhadap Kadar Hormon Adiponektin sebagai Faktor Risiko Terjadinya Diabetes Melitus Tipe 2 - Shenia Verinda Harsa (Majority, 2020)
Cigarette contains chemicals that can damage the human body. There are about 7.000 chemicals contained in cigarette smoke, 250 are known to be harmful components and 69 of it, are carcinogenic. Smoking is a risk factor of health problems, such as cardiovascular, pulmonary, neoplasmic, and endocrine diseases. Smoking is related to hypoadiponectinemia. Adiponectin plays a role in insulin through various interactions. Nicotine contained in cigarettes circulates in systemic and causes oxidative stress. It is characterized by an increase in TNFα and IL-6 in adipocyte cells. TNFα could inhibit adiponectin transcription mediated by c-Jun N-terminal kinase (JNK) which phosphorylates PPARγ thereby reducing its DNA binding activity. Physiologically, PPARγ is involved in the formation and secretion of chaperonin, ErolLα, and DsbA-L proteins. Ero1-Lα can increase the secretion of HMW adiponectin and DsbA-L which works as a disulfide isomerase protein that can arrange adiponectin disulfide bonds for multimerization. Decreased ErolLα and DsbA-L secretions can reduce adiponectin levels. Cytokines IL-6 can inhibit adiponectin transcription in vitro on 3T3-L1 adipocyte cells. Decreased adiponectin levels will reduce the activation of IRS 1/2 which is the main signaling pathway in relation to insulin sensitivity by adiponectin, so insulin resistance will occur. This shows the nicotine content in cigarettes that causes a decrease in plasma adiponectin levels so that insulin resistance occurs, thus smoking becomes one of the risk factors caused by Type 2 Diabetes Mellitus.